Canadian Foreign Policy Decision- Making: A Case-Study of Canadian-Southern African Relations - Brown, Lee Susan (My University, 1974)
The central purpose of this paper is to examlne the Canadian foreign policy decision making process. A case-study approach waS used for greater manageability, but the specific case of relations with Southern Africa was chosen because it is the author's contention that Canadian policy in 1974 towards that area of the world is seriously in error and needs to be changed.
The specifics of Canadian decision-making regarding Southern Africa were applied to a model of decision-making suggested by Salisbury and Heinz, and adapted by Hockin, in which decisions were considered independent variable determining the actual policy process. Policy emerges as a result of the interrelationship between the demand pattern and the cost of decision-making. The model allowed for organization of the research and suggested directions which future actions might take on the issue.
In addition to emphasizing very practical reasons for changing Canadian policy towards Southern Africa, the author also argues strongly that ethical considerations do have a role to play in international and political affairs. More specifically, she accuses liberal thought of being chiefly to blame for the faults of Canadian decision-making, and lays out a program of action to correct them.
Keywords: Political Science; Political Science